Do Scholars-Turned-Businessmen Impact Green Innovation? - Zhao, Jing; Li, Wanming; Zhang, Qian (Frontiers in Psychology, 2022)
This study explores how the academic experience of executives affects green innovation. Using data on executive academic experience from a sample of Chinese listed companies, we explore the relationship between executive academic experience and green innovation using a combination of qualitative and quantitative methods. We find that executive academic experience has a positive impact on green innovation. We also investigate the moderating effect of managerial discretionary factors organizational slack, nature of property rights, and degree of market competition. The results show that organizational slack positively moderates the relationship between senior managers’ academic experience and green innovation, and this positive relationship is more significant in state-owned enterprises. The degree of market competition had a negative moderating effect on the positive relationship between academic experience of senior managers and green innovation. Improved general competence and concern for the environment are two possible mechanisms by which senior managers’ academic experience affects green innovation. Our findings suggest that academic experience of senior managers is an important factor for green innovation in emerging market firms.